2011
DOI: 10.1007/s00271-011-0282-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sustained deficit irrigation on spearmint (Mentha spicata L.) biomass production, oil yield, and oil quality

Abstract: Crop response to deficit irrigation is an important consideration for establishing irrigation management strategies when water supplies are limited. This study evaluated the response of native spearmint to water deficits applied using overhead sprinklers in eastern Washington, US. Five levels of irrigation were applied ranging from full irrigation (100%) to 5% of weekly averaged full crop water needs. Soil water monitoring with soil water balance was used to estimate soil water deficits for irrigation scheduli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 20 publications
2
9
0
Order By: Relevance
“…Different levels of fertilizers may have an impact on the essential oil yield in spearmint, as it has been described previously [23]. Results are in agreement with reports on peppermint from Okwany et al [48], in which essential oil yield remained unchanged across different irrigation regimes at the first harvest, but the deficit regimes revealed a decrease in yield, potentially due to the decreasing trend in fresh mass production.…”
Section: Discussionsupporting
confidence: 91%
“…Different levels of fertilizers may have an impact on the essential oil yield in spearmint, as it has been described previously [23]. Results are in agreement with reports on peppermint from Okwany et al [48], in which essential oil yield remained unchanged across different irrigation regimes at the first harvest, but the deficit regimes revealed a decrease in yield, potentially due to the decreasing trend in fresh mass production.…”
Section: Discussionsupporting
confidence: 91%
“…These results are in parallel to the study of other researchers [23,65,66]. Okwany et al [67] reported a reduction in carvone (7.5%) and an increment in limonene (5%) content after an increase in the deficit irrigation regimes.…”
Section: Organic Compoundssupporting
confidence: 88%
“…The crop has high water demands in summer. Care has to be taken to prevent a waterlogged soil, especially in winter, as this will influence growth [ 52 ].…”
Section: Genus Mentha Plant Cultivationmentioning
confidence: 99%